2019
DOI: 10.1155/2019/2350948
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Contrast Agent in Abdominal CT: Is It Really Needed to Identify the Cause of Bowel Obstruction? Proof of Concept

Abstract: Background. To compare sensitivity of unenhanced computed tomography (CT) and contrast-enhanced CT for the identification of the etiology of bowel obstruction. Materials and Methods. We retrospectively evaluated abdominal CT scans of patients operated for bowel obstruction from March 2013 to October 2017. Two radiologists evaluated CT scans before and after contrast agent in two reading sessions. Then, we calculated sensitivity of CT in the diagnosis of bowel obstruction and determined in which cases the etiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, it is very important to explore a better method for the early diagnosis of strangulated intestinal obstruction. Some recent studies suggested that imaging, such as high-resolution CT [ 23 ], could improve the diagnosis of strangulated intestinal obstruction, but high-resolution CT is a radiological examination that is not suitable for pregnant women or children [ 24 , 25 ]. Moreover, high-resolution CT is expensive and cannot be used to observe the dynamic changes in patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to explore a better method for the early diagnosis of strangulated intestinal obstruction. Some recent studies suggested that imaging, such as high-resolution CT [ 23 ], could improve the diagnosis of strangulated intestinal obstruction, but high-resolution CT is a radiological examination that is not suitable for pregnant women or children [ 24 , 25 ]. Moreover, high-resolution CT is expensive and cannot be used to observe the dynamic changes in patient’s condition.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, computed tomography (CT) is the first choice for diagnosing intestinal obstruction [ 8 ], and is recommended by several studies [ 9 11 ]. However, most studies focused on enhanced CT [ 12 ], which may underestimate the diagnostic value of unenhanced CT [ 13 ].…”
Section: Introductionmentioning
confidence: 99%